The Performance of the Micro Small and Medium Enterprises in India - Singh, Rajinder; Kumar, Mahesh; Upadhyay, Anshika (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
MSMEs have been playing an important role in the overall economic development of a country like India, where millions of people are underemployed or even unemployed. This sector solves many problems, viz. poverty and unemployment, through providing immediate and large-scale employment with lower investments and proves to be the second largest manpower employer after agriculture. Micro-small and medium enterprises (MSMEs) play an essential role in the economic development of the country. It contributed to employment as well as the economic growth of the country. The present study shows the performance of the MSMEs in the state of Uttarakhand in terms of investment and employment. The secondary data has been used in the study. The study found that MSMEs play a significant role in the state's economic development, and the correlation between investment and employment was positive during the study period.